An Enzyme-Linked Immunosorbent Assay (ELISA) Used to Study the Cellular Secretion of Endothelial Plasminogen Activator Inhibitor (PAI-1) - MacGregor, I R; Booth, N A (Thrombosis and Haemostasis, 1988)
A two-site sandwich ELISA was developed to measure PAI-1 antigen and utilised a polyclonal antiserum produced against PAI-1 purified from human endothelial cell secretory products. The assay was calibrated against a preparation of pure PAI-1 whose protein concentration had been determined by amino acid analysis and the detection limit was 30 pg PAI-1 ml“3 sample. PAI-1 was detected in primate sera but not in a wide range of nonprimate sera and no cross-reactivity with α2-antiplasmin or antithrombin III was observed.The ELISA was used to study cellular secretion of PAI-1 which was confirmed as a major secretory protein in human umbilical vein endothelial cells (HUVEC). PAI-1 antigen accumulated in the medium in a linear fashion with time and accounted for ≃10% of total secreted protein. Specific activity of intracellular PAI1 was typically 20-fold greater than that of PAI-1 in 24 h conditioned medium and a t½ for inactivation of secreted PAI-1 of 0.53 h was calculated. Purified endotoxin stimulated the secretion of PAI-1 antigen and raised the intracellular levels in HUVEC cultures showing that the anti-fibrinolytic actions of endotoxin are effected by increasing the rate of synthesis and secretion of PAI-1.
Keywords: ELISA; Plasminogen activator inhibitor; Endothelial; Cell cultures